DNA viruses and Langerhans Cell Histiocytosis in Iranian Children - M Kazemi Aghdam; SAR Naji; M Khodami (Majallah-i Dānishgāh-i ʻUlūm-i Pizishkī̄-i Bābul, 2017)
BACKGROUND AND OBJECTIVE: Viruses are suggested as possible etiologic factor of Langerhans cell histiocytosis (LCH) by some investigators. Nonetheless, no report was found on this subject in Iranian children. We looked for the presence of Epstein-Barr virus (EBV), human herpesvirus-6 (HHV-6), herpes simplex virus (HSV) types 1 and 2, and Cytomegalovirus (CMV) in children with LCH. METHODS: The investigation in this retrospective study, was for the presence of HHV-6 DNA in 48 patients and CMV, HSV types 1 and 2 and EBV DNA in 30 patients with LCH, using paraffin-embedded tissue samples and 48 and 30 (respectively) age and tissue-matched controls from the department of pediatric pathology, using nested polymerase chain reaction (nested-PCR for HHV-6 and HSV types 1 and 2), qualitative PCR method (for CMV) and qualitative TaqMan Real-time PCR (for EBV). FINDINGS: HHV-6 was found in one (2.1%) patient and six (12.5%) control specimen (P= 0.11, OR: 0.15; 95%CI: 0.02-1.29). Two (6.66%) patients and one (3.3%) control sample had CMV, with a P value of 1.0, and OR: 2.07; 95% CI of OR: 0.18-24.15. We did not find HSV types 1 and 2 DNA in any of the patients or controls. EBV was detected in 19 (63.33%) patients and 8 (26.7%) control group. P value was 0.004 with Odds Ratio: 4.75; 95% CI of OR: 1.58-14.25. CONCLUSION: CMV, HSV types 1 and 2, and HHV6 do not appear to have any role in the pathogenesis of LCH. However, considering the statistically significant p=0.004, our findings suggest a possible position for EBV in the pathogenesis of LCH in Iran.